Improving Learning Outcomes of Grade 4D Students in Islamic History Using Mind Mapping Learning Media at Pondok Modern Darussalam Gontor - Usman Agustin; A’isyatu Makarimil Chasna; Wahyuningtyas Islami; Fauziah Rozifatul Haq (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
The subject of Islamic History is one of the Islamic education subjects taught at Pondok Modern Darussalam Gontor Putri 2. However, the learning process is currently limited to transferring knowledge, making it seem dull. Additionally, the textbooks used by the 4th-grade female students have shortcomings, such as the lack of practice questions and a less engaging book design. Therefore, given these conditions, the researcher aims to find a solution to achieve the intended learning objectives. In this regard, the researcher, also an observer, is obligated to create an engaging, creative, and enjoyable learning environment for the students. One approach is by using the mind map learning method, where the teacher prepares and presents a colorfully designed map during the learning activities to capture the students' attention. The purpose of using this media is to stimulate the students' thinking and train them to extract wisdom and values from the learning material. Based on the data obtained from the per-cycle results, there has been an improvement in the learning process in two aspects: student engagement and the completeness of learning outcomes. In terms of student engagement, during cycle 1, 21 students were actively paying attention and asking questions related to the lesson. In cycle 2, there was an increase, with 32 students actively participating in learning. Regarding the benchmark for the completeness of learning outcomes, in cycle 1, 25% of the total students scored above 60. In cycle 2, this increased to 80% of the total students. This indicates that the mind map method can enhance student engagement in the learning process and improve the completeness of learning outcomes.